Facilitating technology adoption in the NHS: negotiating the organisational and policy context - a qualitative study - Sue Llewellyn; Rob Procter; Gill Harvey; Gregory Maniatopoulos; Alan Boyd (National Institute for Health Research, 2014)
Background: Proven clinical effectiveness and patient safety are insufficient to ensure adoption and implementation of new clinical technologies. Despite current government policy, clinical technologies are not yet demand-led through commissioning. Hence, adoption and implementation relies on providers. Introducing new technologies initially raises providers' costs as they necessitate training, alter patient pathways and change patient management, and may lead to reduced patient throughput in the short term. The current funding regime for providers - Payment by Results (PbR) - rewards activity. It is not surprising, therefore, that providers often see new technologies as risky. Objectives: This study investigated the organisational and policy context for the adoption and implementation of clinical technologies, because this context may present barriers that slow - or even prevent - uptake. The research focused on three clinical technologies: insulin pump therapy (IPT); breast lymph node assay (BLNA), a diagnostic tool for metastases; and ultrawide field retinal imaging (UFRI). The implementation of these technologies had been supported by NHS Technology Adoption Centre (NTAC). Methods: The research method was qualitative case studies of these three clinical technologies. The primary data collection technique was semistructured interviews of NTAC staff, clinicians, managers and commissioners, supplemented by documentary evidence, participant and non-participant observation of meetings and videos. For IPT, we also conducted a survey of clinicians and analysed anonymised e-mails from patients. Results: NHS providers did not perceive any central 'push' from the Department of Health or the National Institute for Health and Care Excellence (NICE) to adopt, implement or diffuse new clinical technologies. There is a 'bottom-up' adoption culture: any trust could choose to adopt any, all or none of the three clinical technologies we investigated. This is undesirable, as clinically efficacious technologies should be equally available to all patients. Where there is NICE guidance, this acted as an enabler for adoption, but some trusts still did not offer IPT despite this. We found that PbR could be a major obstacle to adoption. Our evidence also indicates that, contrary to its intention, commissioning practice is more of a barrier than an enabler of innovation. Protracted negotiations over funding between providers and commissioners delayed implementation of BLNA and IPT. Organisational power and politics between hospitals and community-based services was a significant barrier for adoption of UFRI. Clinicians outside of specialist ophthalmology centres did not understand the clinical utility of UFRI (e.g. its diagnostic potential or how and when to use it). Conclusions: NTAC was successful in assisting trusts over the generic organisational barriers outlined above, particularly with regard to taking responsibility for the logistics of implementation, negotiating new patient pathways and ways of working with relevant stakeholders, and using their skills in project management and stakeholder engagement to drive processes forward. Where there were major obstacles, however, the NTAC process stalled. 'Bottom-up' adoption at individual trusts needs to be linked into wider national processes that offer vision, some central direction, further assessment and evaluation, and the infrastructure to ensure diffusion to sites that have the capabilities and capacities to best utilise the clinical technology. Funding: The National Institute for Health Research Health Services and Delivery Research programme.